Shah Waliullah Dehlawi and His Intellectual Contributions: A Study (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Qutb uddin Ahmad ibn Abdur Rahim al- Umari ad- Dehlowi, commonly known as Shah Walullah Dehlowi, was an Islamic Sunni Scholar and Sufi reformer. Shah Waliullah was an exceptional individual, who has undoubtedly made the greatest social, political, religious, literary, and intellectual contributions to the development of thought in south-east Asia. Shah Waliullah, without doubt struggled for the improvement of Muslims. He urged the Muslims to refrain from false practices, exhorted them to unite and not to divide on insignificant differences. Shah Waliullah left a lasting legacy behind and indeed is and always will be a source of inspiration for generations to come. His contributions and renaissance of the Muslims positively impacted those in his time continues to do so. Shah Waliullah’s reformist ideas profoundly impacted those of his time to such an extent that the annals of history of Southeast Asia cannot be discussed without referring to his influence. Even the various schools of thought and reformist movements of our time, especially those linked to the subcontinent revere him and have pride in boasting their origins back to his teaching and claim his intellectual and spiritual influence.In this study, we shall try our best to explore the contributions of Shah waliullah Dehlowi in every side of the society.